THE IMPORTANCE OF DIGITAL TECHNOLOGIES IN THE PROCESS OF IMPROVING THE QUALITY OF STUDENT EDUCATION IN THE HIGHER EDUCATION SYSTEM (Universal International Scientific Journal, 2026)
This article discusses the importance, characteristics, and contribution of digital technologies to improving the quality of education for students in the higher education system, as well as the achievements made with these technologies. It also presents the views of our President on the importance of digital knowledge and technologies in improving the quality of education and achieving progress.
Keywords: digital knowledge, digital technologies, quality of education, artificial intelligence, globalization, distance learning, personalized learning, development, progress, internet.